Phenotypic diversity and immunodeficiency in Trichohepatoenteric Syndrome: a case series analysis - Mohamed Nashrudin, Khairoon Nisa; Ismail, Intan Hakimah; Zainal Abidin, Mohd Azri; Zakaria, Noorzeehan; Safwan, Muhammad Shafiq; Abdul Jabar, Siti Wardah; Ramli, Farizza Hazlin; Thong, Pui Ling; Ng, Ruey Terng; Ong, Sik Yong (2024)
Trichohepatoenteric Syndrome (THES) is a rare autosomal recessive disorder caused by mutations in the TTC37 or SKIV2L genes, characterised by chronic intractable diarrhoea in infancy, woolly hair, facial dysmorphism, failure to thrive, recurrent infections, and, in some cases, liver and platelet abnormalities. Immunologically, THES is often associated with hypogammaglobulinemia, necessitating immunoglobulin supplementation. Recent studies have identified additional immunological defects, including reduced switched memory B cells, decreased T and NK cell counts, and impaired T cell proliferation. The clinical presentation of THES is highly variable, and there is currently no specific treatment available. This case series describes two paediatric patients with THES, highlighting their phenotypic diversity, immunodeficiency, and the genetic basis of their condition.